2018
DOI: 10.1016/j.idcr.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of listeria rhombencephalitis

Abstract: Listeria rhombencephalitis (LRE) is a rare encephalitis of the hindbrain that can present with a variety of neurological symptoms. It is a diagnostic challenge, but prompt antimicrobial therapy is important to prevent high rates of mortality and morbidity. We report two cases of LRE, with several contrasting clinical features and different disease courses. Despite being rare, it is important to consider listeria in patients with possible meningoencephalitis, even if cultures are negative. Empirical treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
(49 reference statements)
0
18
0
2
Order By: Relevance
“…However, Veesenmeyer and Edmondson, among others, do not recommend the use of ampicillin as empirical treatment for newborn infections after the first week of life because of the low morbidity of listeriosis and high level of antimicrobial resistance of Gram-negative bacteria (Veesenmeyer and Edmonson, 2016); therefore, it is important to diagnose and treat perinatal listeriosis early. As not all samples from listeriosis patients are positive (Mansbridge et al, 2017), contributing to a delay in diagnosis of listeriosis, it is advisable to culture multiple types of sample for listeriosis initially (Awofisayo-Okuyelu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, Veesenmeyer and Edmondson, among others, do not recommend the use of ampicillin as empirical treatment for newborn infections after the first week of life because of the low morbidity of listeriosis and high level of antimicrobial resistance of Gram-negative bacteria (Veesenmeyer and Edmonson, 2016); therefore, it is important to diagnose and treat perinatal listeriosis early. As not all samples from listeriosis patients are positive (Mansbridge et al, 2017), contributing to a delay in diagnosis of listeriosis, it is advisable to culture multiple types of sample for listeriosis initially (Awofisayo-Okuyelu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Listeria monocytogenes and other infectious inflammatory causes are often cited as the most common etiology of RE (10,11). However, some studies have reported a higher proportion of immunological causes among RE cohorts (4,8).…”
Section: Discussionmentioning
confidence: 99%
“…Rhombencephalitis (RE) affects individuals of all ages, sex, ethnicity, and immune status (4,8,9). Listeria monocytogenes and other infectious inflammatory causes are often cited as the most common etiology of RE (10,11). However, some studies have reported a higher proportion of immunological etiologies, causing autoimmune RE (4,8).…”
Section: Discussionmentioning
confidence: 99%